2014
DOI: 10.1016/j.neuron.2014.07.022
|View full text |Cite
|
Sign up to set email alerts
|

A Common Structure Underlies Low-Frequency Cortical Dynamics in Movement, Sleep, and Sedation

Abstract: SummaryUpper-limb movements are often composed of regular submovements, and neural correlates of submovement frequencies between 1 and 4 Hz have been found in the motor cortex. The temporal profile of movements is usually assumed to be determined by extrinsic factors such as limb biomechanics and feedback delays, but another possibility is that an intrinsic rhythmicity contributes to low frequencies in behavior. We used multielectrode recordings in monkeys performing an isometric movement task to reveal cyclic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
159
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(172 citation statements)
references
References 49 publications
12
159
1
Order By: Relevance
“…2). Note the similarity of the matrices shown in C and programs that are recruited to perform tasks (4,5,69). Thus, lag threads may form the basis for activity sequences that naturally play out in responses to events.…”
Section: Part IImentioning
confidence: 99%
“…2). Note the similarity of the matrices shown in C and programs that are recruited to perform tasks (4,5,69). Thus, lag threads may form the basis for activity sequences that naturally play out in responses to events.…”
Section: Part IImentioning
confidence: 99%
“…Slow oscillations (<15 Hz) repeated the behavioral pattern of REM sleep alterations (i.e., a persistent increase throughout SR1 to SR5, whereas high-frequency oscillations showed progressive increases over the course of CSR). CFC of slow and fast oscillations during REM sleep were preserved or even enhanced in CSR with a matching topography [i.e., a prominent (8-10 Hz) theta2-gamma2 (70-90 Hz)] nesting was detected in the areas overlaying the hippocampus, narrow-band delta range oscillations (2 and 4 Hz) were modulating gamma1 (35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45) in the PFC and a weaker slow (∼1 Hz) modulation of beta2 (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) was observed in the sensory-motor area. Collectively, these findings suggest that in REM sleep, slow oscillations closely following the behavioral pattern imposed by REM sleep regulation may serve to translate this top-down homeostatic control to a wide range of cortical networks whereas fast oscillations escaping this control might serve as an instrument granting relative independence for local ensembles to synchronize on shorter spatiotemporal scales.…”
Section: Discussionmentioning
confidence: 99%
“…Beta power (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30). Overall, beta activity after SR1 was similar to BL but then gradually increased in subsequent days in the somatosensory cortex (not significant on SR1 and SR3; P = 0.009 on SR5; Table S3).…”
Section: Persistent Increase In Rem Sleep Time Rebounds After Repetitivementioning
confidence: 95%
“…First, recent work has suggested that the neural activity controlling voluntary movement is intrinsically rhythmic at ϳ3 Hz (Churchland et al 2012;Hall et al 2014). Thus the two phases of EMG activity described here may reflect an underlying rhythmicity in the neural control of the upper extremity musculature.…”
Section: Implications For the Neural Control Of Reach-to-grasp Movementsmentioning
confidence: 73%